Study achievement for students with kids - Daniel Hallberg; Thomas Lindh; Jovan éZamac (Institute for Labour Market Policy Evaluation (IFAU), 2011)
In this paper we explore the composition of students, the study length towards diploma, and examine the likelihood of diploma, all with respect to parenthood. Few get children while enrolled in higher education, nevertheless one fourth of female university students in Sweden has children. In Sweden as in many other countries enrollment periods have been prolonged and allocated to later parts of life. Using a large longitudinal register micro data set containing educational achievement we find that students with children seem to be somewhat more efficient in their studies among those who have graduated. Becoming parent speeds up ongoing studies but not studies that are initiated after entry into parenthood. We also find an indication that students with children have a lower dropout rate since their probability to register a diploma is higher, compared to students without children.
Keywords: J13; J31; I21; 330; Students; parenthood; education; study interruption; Bildungsverhalten; Studierende; Eltern; Bildungsabschluss; Schweden